Regulasi Negara Terhadap Ketentuan Pembayaran Biaya Sebelum Nikah: Perspektif Hukum Tata Negara dan Hukum Islam - Firmansyah, Dimas; Pangesti, Elza Qorina (STAI Bumi Silampari, 2025)
This study examines the Islamic legal review of the provisions of payment of customary fees before the marriage contract (case study in Batugajah Village, Rupit District, North Musirawas Regency , south sumatera), the formulation of the problem studied in this study is how the practice of the provisions of payment of customary fees before the marriage contract, especially in Batugajah Village, Rupit District, North Musirawas Regency and how the Islamic legal review of the provisions of payment of customary fees before the marriage contract. The purpose of this study is to determine the practice of the provisions of payment of customary fees before the marriage contract, especially in Batugajah Village Batugajah Village and to determine the Islamic legal review of the provisions of payment of customary fees before the marriage contract. The research method used in this study is qualitative research. The data collection techniques used in this study are observation, interviews, and documentation, while the data analysis used by the researcher includes using deductive data analysis. The research location in this study is in